An injury audit in high-level male youth soccer players from English, Spanish, Uruguayan and Brazilian academies. (July 2020) - Hall, Elliott C.R.; Larruskain, Jon; Gil, Susana M.; Lekue, Jose A.; Baumert, Philipp; Rienzi, Edgardo; Moreno, Sacha; Tannure, Marcio; Murtagh, Conall F.; Ade, Jack D.; Squires, Paul; Orme, Patrick; et al.
Abstract: Objectives: To identify the most common injury types/locations in high-level male youth soccer players (YSP). Design: Prospective cohort surveillance study. Setting: Professional soccer club academies. Participants: Six hundred and twenty-four high-level male YSP [Under 9 (U9) to U23 year-old age groups] from academies in England, Spain, Uruguay and Brazil. Main outcome measures: Injury type, location and severity were recorded during one season. Injury severity was compared between age groups, while injury type and location were compared between nations. Results: Four hundred and forty-three training or match injuries were recorded, giving an injury rate of 0.71 per player. Non-contact injuries were most common (58.5%), with most (44.2%) resolved between 8 and 28 days. Most injuries (75.4%) occurred in the lower limbs, with muscle (29.6%) the most commonly injured tissue. U14 and U16 suffered a greater number of severe injuries relative to U12 and U19/U20/U23/Reserves. Tendon injury rate was higher in Brazil vs. Spain (p < 0.05), with low back/sacrum/pelvis injury rate highest in Spain (p < 0.05). Conclusions: The proportion of severe injuries in U14 and U16 suggests YSP injury risk is maturation-dependent. Minimal differences in type and location between high-level YSP from four different countries suggest injury rates in this population are geographically similar. Highlights: Muscle injuries were the most common injury type in 624 youth soccer players. The thigh was the most common injury location sustained in a single season. Injury type and location were similar in players playing in different countries. Players in the U14 and U16 age groups suffered relatively more severe injuries. This suggests maturation affects injury risk in this under-researched population.